Sintese e caracterização de líquidos iônicos próticos com base catiônica 2-hidroxi-etilamônio: solubilidade de corantes têxteis - Biggi, Alessandra Brandani (2013)
This paper focuses on solubility measurements of textile dyes (acidic, disperse and reactive) synthesized in ionic liquids in a temperature range from 40 ° C to 80 °C. Measurements of solubility were performed in UV-Vis spectrophotometer. The ionic liquids synthesized were protic 2-hydroxy ethylammonium acetate (2HEAA), 2-hydroxy ethylammonium propionate (2HEAPr), 2-hydroxy ethylammonium butanoate (2HEAB) and 2-hydroxy ethylammonium pentanoate (2HEAPe). Conventional methods were used for synthesis and purification of ionic liquids. NMR spectra (nuclear electromagnetic resonance) establish the structure of ionic salt. In the study, the physicochemical characterization of ionic liquids were investigated: viscosity, density, ionic conductivity, thermal gravimetric analysis and water content. According to the results obtained in these studies and the results obtained by many authors with respect to the characterizations mentioned above, it was found that showed the same behavior as the characteristics of some protic ionic liquids. In the compounds studied, the anions have a strong effect on the measurements of solubility and physicochemical properties. For all ionic liquids studied, there is an inverse relationship between temperature and its properties. From the results obtained it was observed that the density and viscosity decrease with increasing temperature, the opposite was observed for measurements of conductivity and solubility of textile dyes. Based on the obtained experimental data in this work, together with the low cost, simplicity of expressive synthesis and solubility of ionic liquids in textile dyes studied, we see a huge potential application due to the possibility of replacing the solvent commonly used in large quantities in textile dyeing, water, an organic solvent, the protic ionic liquid in dyeing textile fibers.